2010
DOI: 10.1183/09031936.00125810
|View full text |Cite
|
Sign up to set email alerts
|

Parameters affecting pharyngeal response to genioglossus stimulation in sleep apnoea

Abstract: Chronic stimulation of the hypoglossus nerve may provide a new treatment modality for obstructive sleep apnoea (OSA). In previous studies we observed large differences in response to stimulation of the genioglossus (GG). We hypothesised that both individual patient characteristics and the area of the GG stimulated are responsible for these differences.In the present study, we compared the response to GG electrical stimulation at the anterior area (GGa-ES), which activates the whole GG and the posterior area (G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 42 publications
2
36
0
2
Order By: Relevance
“…These findings of multilevel opening at the different collapsible levels of the upper airway with stimulation probably explain the effectiveness of UAS therapy in reducing AHI severity in a recent multicentre, prospective trial evaluating this UAS therapy, as well as explain the return to baseline AHI in patients who were randomised to therapy withdrawal [15]. The findings of improvement in upper-airway cross-sectional area at the retropalatal level during unilateral hypoglossal nerve stimulation are in line with the results from groups visualising retropalatal area during direct genioglossus muscle stimulation under anaesthesia [6,8], as well as others visualising palatal anterior displacement and thinning from fluoroscopic images during intraoperative testing of an implantable hypoglossal neurostimulator [16]. The present study found this result in patients undergoing a therapeutic clinical trial.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…These findings of multilevel opening at the different collapsible levels of the upper airway with stimulation probably explain the effectiveness of UAS therapy in reducing AHI severity in a recent multicentre, prospective trial evaluating this UAS therapy, as well as explain the return to baseline AHI in patients who were randomised to therapy withdrawal [15]. The findings of improvement in upper-airway cross-sectional area at the retropalatal level during unilateral hypoglossal nerve stimulation are in line with the results from groups visualising retropalatal area during direct genioglossus muscle stimulation under anaesthesia [6,8], as well as others visualising palatal anterior displacement and thinning from fluoroscopic images during intraoperative testing of an implantable hypoglossal neurostimulator [16]. The present study found this result in patients undergoing a therapeutic clinical trial.…”
Section: Discussionsupporting
confidence: 69%
“…Therapeutic applications using neuromuscular electrical stimulation of the hypoglossal nerve and genioglossus muscle have been designed and evaluated as a potential alternative to positive airway pressure therapy and upper-airway surgical procedures [6][7][8][9][10][11][12][13]. The therapy consists of an implanted, programmable neurostimulation system, with a stimulation electrode around the protrusor branches of the right hypoglossal nerve and a respiration sensor placed in the right intercostal space to detect respiration [10,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that we have previously found that the mechanical effect of GG stimulation during sleep and anaesthesia is similar [33]. Moreover, the site used for electrode placement in the current study produces a substantially smaller effect than a location that activates preferentially the protrusive GG fibres [34]. In addition, electrical stimulation produces a much smaller protrusive force than volitional activation [35].…”
Section: Glottismentioning
confidence: 49%
“…Nevertheless, lack of adequate activation of muscles not evaluated in this study cannot be excluded. Anaesthesia-induced general hypotonia that includes the trunk and neck muscles may affect the forces arising from the chest and increase extrapharyngeal pressure within the maxillo-mandibular bony structures that enclose the soft tissue surrounding the collapsible segment of the pharynx [34,40]. Such alterations may affect GG contraction and/or the negative dependence of flow and downstream pressure.…”
Section: Sleep-related Disorders Y Dotan Et Almentioning
confidence: 99%
See 1 more Smart Citation